Elizebeth Smith Friedman and one example of a prohibition era encryption system. Issue 3 (4th May 2023) - Boersma, Stuart
Abstract: A short ciphertext message encrypted using a Prohibition era encryption system is examined. First published in David Kahn's The Codebreakers, this example appears in two early reports written by Elizebeth Smith Friedman. Some obvious and some not so obvious errors are identified and corrected when possible. Friedman's cryptanalysis of the ciphertext is given.